Knowledge management model for the national schoolar feeding program Qali Warma - Simón-Díaz, Blanca F. (2020)
This research shows the results of the research developed, whose objective was to design a knowledge management model for the Huánuco SFPQW. The research was divided into two phases: the first qualitative, which allowed developing the proposed conceptual model and the second quantitative, which empirically confirmed the conceptual model. It was analyzed through case studies in 3 areas of the SFPQW with semi-structured interviews addressed to the bosses of mentioned areas, also through direct observation and documentation of the SFPQW. It was explored empirically the way through which workers employed the knowledge management and through this was developed the model divided in three phases: the generation, transfer and integration of knowledge. The conceptual model obtained was empirically contrasted using a population of 19 collaborators from different areas; the Chi square statistical test was applied to verify the organizational and individual elements of the knowledge management process. The results show that knowledge management depends on the workers, their organizational culture and management style; the transfer of knowledge depends on an open and receptive organizational culture and a directive style that generates participation towards integration of knowledge to foment on an organizational culture that promotes the assimilation of knowledge in collaborators.